2020
DOI: 10.3390/genes11111275
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Metamizole-Induced Agranulocytosis in European Populations

Abstract: Agranulocytosis is a rare yet severe idiosyncratic adverse drug reaction to metamizole, an analgesic widely used in countries such as Switzerland and Germany. Notably, an underlying mechanism has not yet been fully elucidated and no predictive factors are known to identify at-risk patients. With the aim to identify genetic susceptibility variants to metamizole-induced agranulocytosis (MIA) and neutropenia (MIN), we conducted a retrospective multi-center collaboration including cases and controls from three Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 97 publications
(123 reference statements)
0
14
0
Order By: Relevance
“…Thus, the study of the genetic basis of ADR has to consider the complex interplay between the genetic information and environmental factors in a given disease condition (Afsar et al, 2019). Finally, it must be considered that the huge variability of genetic information is transmitted from one generation to the other, not always unaltered, inserting a further degree of variability, with possible great clinical relevance (Cismaru et al, 2020).…”
Section: Role Of Genetic Codification In Adverse Drug Reactionsmentioning
confidence: 99%
“…Thus, the study of the genetic basis of ADR has to consider the complex interplay between the genetic information and environmental factors in a given disease condition (Afsar et al, 2019). Finally, it must be considered that the huge variability of genetic information is transmitted from one generation to the other, not always unaltered, inserting a further degree of variability, with possible great clinical relevance (Cismaru et al, 2020).…”
Section: Role Of Genetic Codification In Adverse Drug Reactionsmentioning
confidence: 99%
“…The most promising single-nucleotide polymorphisms that met marginal significance in a joint metaanalysis were rs55898176 and rs4427239, the latter located in SVEP1 (Sushi, von Willebrand factor type A, EGF and pentraxin domaincontaining protein 1), a gene previously implicated in hematopoiesis. 9 Aside from the life-threatening risk of agranulocytosis, anaphylaxis is a feared risk of metamizole. The estimates of incidence are 8.1 (3.5-19) per 10,000 exposed patients and are thus much higher compared with the risk of agranulocytosis, but in a range similar to diclofenac's incidence of 7.2 (2.6-20) cases of anaphylaxis per 10,000.…”
Section: The Uncertainties Of Metamizole Usementioning
confidence: 99%
“…As clozapine‐induced agranulocytosis was shown to be associated with the presence of specific HLA‐alleles, 8 similar attempts have been made in three European populations for metamizole‐induced agranulocytosis, however without revealing strong results. The most promising single‐nucleotide polymorphisms that met marginal significance in a joint meta‐analysis were rs55898176 and rs4427239, the latter located in SVEP1 (Sushi, von Willebrand factor type A, EGF and pentraxin domain‐containing protein 1), a gene previously implicated in hematopoiesis 9 …”
mentioning
confidence: 99%
“…In addition to the GWAS by Cismaru et al [ 1 ], several candidate gene pharmacogenomic studies were also reported in this Special Issue. For example, de Carvalho et al [ 2 ] employed a targeted genotyping panel of candidate genes and variants to study children from Brazil with acute lymphoblastic leukemia (ALL) undergoing chemotherapy with 6-mercaptopurine (6-MP) and methotrexate (MTX).…”
mentioning
confidence: 95%
“…Cismaru et al [ 1 ] performed a genome-wide association study (GWAS) to identify genetic variants implicated in metamizole-induced agranulocytosis (MIA) and neutropenia among three European populations. In their joint meta-analysis of MIA cases across all cohorts, two candidate loci on chromosome 9 were identified, rs55898176 (OR = 4.01, 95% CI: 2.41–6.68, p = 1.01 × 10 −7 ) and rs4427239 (OR = 5.47, 95% CI: 2.81–10.65, p = 5.75 × 10 −7 ).…”
mentioning
confidence: 99%